The roles of alkyl halide additives in enhancing perovskite solar cell performance - Chueh, Chu-Chen; Liao, Chien-Yi; Zuo, Fan; Williams, Spencer T.; Liang, Po-Wei; Jen, Alex K.-Y. (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Alkyl halide additives have been investigated to elucidate their effects in enhancing perovskite solar cell performance. We found that the additives can participate in the perovskite formation via dissociated halides, suggesting that molecular structure of alkyl halide additives plays multiple roles in modulating the dynamics of perovskite crystal growth.